Os instrumentos do Instituto Soft Law como ferramentas para a afirmação do novo enfoque capitalista - Wagner, Everton da Costa (2022)
The strengthening of large companies called transnationals has brought positive economic development to part of the world's population. However, another part of society was absolutely excluded from growth. Now, faced with the alarming context of inequality that we are experiencing, even more aggravated by the effects of the health crisis that is ravaging the world, it is necessary to think about the inclusion of these people to a minimally dignified life. The set of social rights is, today, all over the world, severely shaken due to the effects of capitalist globalization. In fact, a situation of social exclusion of entire populations was created. What is happening in all parts of the world is that the working mass has become a perfectly dispensable input in the capitalist system of production. The great challenge posed, therefore, for the current and, above all, for the next and future generations is to know if humanity will be able to guide these transformations towards the construction of a better world, or, if the progress and the development will continue to be dominated and exploited only by those in power. Hence, it is relevant to the legal analysis of a new capitalist approach from the perspective of human rights, with the objective of finally realizing the dignity of the human person as an aspect of an economic regime. This analysis, in our view, must be done from the perspective of humanist capitalism, which proposes the transposition of the economic regime to the Christian perspective, shifting the concepts of the Universal Law of Fraternity to Economic Law. The novel theory encourages the recognition of human rights, as well as their three-dimensional realization, translating into the maxim that the planet will, finally, be more peaceful and civilized to the extent that the full realization of these rights is actually achieved. However, a problem deserves to be highlighted: for many, there are no norms capable of guaranteeing the concreteness of this novel theory. In this context, the present work aims to analyze soft law instruments as possible tools capable of assisting in the affirmation of this economic regime governed by humanist capitalist theory. The use of such an institute allowed normative changes following more effectively the changes that the modern world demands today, which will result in the establishment of a standard of conduct that has the potential to avoid the anachronism of Law in the face of the strengthening of these large transnationals.